Controle para um veículo aéreo não tripulado do tipo quadricóptero - Dantas, Flávia Elionara Freire (Brasil, 2017)
Research on Unmanned Aerial Vehicles (UAVs) has been intensified since the 2000s with the aim of replacing manned vehicles. Its maneuverability makes it capable of handling various types of applications such as surveillance of a particular area, inspection of structures, in difficult to access environments, among others. When the first research began, this type of aerial vehicle was only used for military applications, but at the moment they are studied for other applications; the studies focus on control techniques for stability and flight autonomy. This work aimed the development of an altitude control and attitude of a UAV type quadrotor; the implementation was carried out on the Arduino platform and the flight tests indoors. Design of stability and height control, comparisons between two types of height control, PID (Proportional-Integral-Derivative) and Fuzzy in a Simulink® / MATLAB environment were performed
Keywords: VANT; Controle Fuzzy; Voo Autônomo; Quadricóptero; UAVs; Fuzzy Control; Autonomous flight; Quadrotor; ENGENHARIAS::ENGENHARIA ELETRICA